Synthesis, Spectral and Dissociation Thermodynamics Studies of Cobalt (II), Nickel (II) and Copper (II) Complexes with 2-Hydroxyacetophenone Derivatives - Naser, Juman Ahmed (Al-Nahrain Journal of Science, 2018)
The ketone 2-hydroxyacetophenone was treated with ammonia gas and hydroxylamine hydrochloride for the synthesis of its Schiff base and oxime respectively. The two ligands were used to synthesize Co(II), Ni(II) and Cu(II) complexes. The ligands and complexes have been characterized by IR and UV spectroscopy. Elemental analyses have been performed using C. H. N. for ligands and atomic absorption technique for complexes. The limiting molar conductivity of [M(HANH)2] and [M(HAO)2] complexes in DMF and DMSO at different temperature was measured. The dissociation constant, thermodynamic parameters of dissociation (ΔG, ΔH and ΔS) and the activation energy of the transport process (Ea) were calculated and discussed. The results show that the dissociation constant values in DMF are larger than that in DMSO. The dissociation process is endothermic for all complexes.